An approach for daylight calculation of a building integrated photovoltaic (BIPV) Façade. (4th July 2018) - He, Yi; Schnabel, Marc Aurel
ABSTRACT: Contemporary use of Building Integrated Photovoltaics (BIPV) façades is increasing rapidly. However, A BIPV façade can impact natural lighting because of opaque solar cells in the panels. This paper explicates an approach for daylight calculation in an indoor environment with the BIPV facade system installed. A brief review of daylight calculation is given to reveal the drawbacks of previous methods that are not suitable for our situation, which includes a BIPV façade and requires manual calculation. The detailed calculation, including the mathematical formulas used at each stage, is explained. First, the position of the sun is calculated. Second, we calculate the daylight availability. Our third calculation is of sun and sky illuminance on the ground and vertical façade. This is followed by the calculation of reflected light. As a result, indoor illuminance can be calculated. In the section of results and discussion, theoretical simulations are accomplished with parametric tools. In the comparison, results from the simulation and the calculation are matched, especially in the case of the overcast sky. By these means our approach can be proved effective. In summary, our research provides an accurate and quick approach of daylight calculation, with due consideration given to practical factors in various aspects.